2015
DOI: 10.1073/pnas.1416418112
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-targeting agents augment the toxicity of DNA-damaging agents by disrupting intracellular trafficking of DNA repair proteins

Abstract: The paradigm that microtubule-targeting agents (MTAs) cause cell death via mitotic arrest applies to rapidly dividing cells but cannot explain MTA activity in slowly growing human cancers. Many preferred cancer regimens combine a MTA with a DNA-damaging agent (DDA). We hypothesized that MTAs synergize with DDAs by interfering with trafficking of DNA repair proteins on interphase microtubules. We investigated nine proteins involved in DNA repair: ATM, ATR, DNA-PK, Rad50, Mre11, p95/NBS1, p53, 53BP1, and p63. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(132 citation statements)
references
References 40 publications
7
115
2
Order By: Relevance
“…The number of cells in Sub-G1 not exceed 2% during 72 hours of incubation. Vincristine sulfate, as expected, produced an arrest in G2/M phase of the cell cycle of A549 cells, avoiding cell proliferation and hence causing cell death (Poruchynsky et al, 2015), as was evidenced in a time dependent manner of drug treatment. Instead, the chloroformic fraction from petroleum ether extract of inflorescences, chloroformic fraction from petroleum ether extract of leaves and chloroformic fraction from ethanolic extract of leaves, caused cell growth inhibition of A549 cells by blocking the G1 phase to S phase in the cell cycle (Fig.…”
Section: Resultssupporting
confidence: 76%
“…The number of cells in Sub-G1 not exceed 2% during 72 hours of incubation. Vincristine sulfate, as expected, produced an arrest in G2/M phase of the cell cycle of A549 cells, avoiding cell proliferation and hence causing cell death (Poruchynsky et al, 2015), as was evidenced in a time dependent manner of drug treatment. Instead, the chloroformic fraction from petroleum ether extract of inflorescences, chloroformic fraction from petroleum ether extract of leaves and chloroformic fraction from ethanolic extract of leaves, caused cell growth inhibition of A549 cells by blocking the G1 phase to S phase in the cell cycle (Fig.…”
Section: Resultssupporting
confidence: 76%
“…Recent evidence suggests an important nonmitotic function of 2-ME2, in preventing the nuclear accumulation of transcription factors or DNA repair proteins (41,42). We therefore quantitated SCL at the single-cell level by flow cytometry and found that 2-ME2 caused a dose-dependent inhibition of the human SCL oncoprotein in SCL tg LMO1 tg pre-LSCs ( Figure 4C).…”
Section: -Me2 Inhibits Scl Accumulation and Transcriptional Activitymentioning
confidence: 87%
“…One study showed that in prostate cancer cells, taxanes act, at least in part, by inhibiting nuclear transport of the androgen receptor (AR), and hence block AR-mediated signaling [34]. It was also recently reported that MTAs interfere with the trafficking of DNA repair proteins on interphase microtubules, providing a mechanistic explanation for the long-standing observation that MTAs and DNA damaging agents act synergistically [35]. We observed that the induction of apoptosis in primary ALL cells in G1 phase was not initiated until 24 h after vincristine treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%